Teacher education : dilemmas and prospects - Thomas, Elwyn (New York : Routledge, 2002)
The 2002 yearbook examines four key areas of teacher education within the context of present dilemmas and future prospects: 1. Theories, models and ideologies of teacher education; 2. the control of teacher education by the state, and the role of schools and higher education; 3. cultural perspectives and the education of teachers; 4. continuities in teacher education.All four areas are closely intertwined in most countries, and this volume reflects on current issues that arise from these issues. The contributors focus on issues of improving levels of educational quality, effectiveness in training modes, and the way future strategies of teacher education relate to processes of modernization and globalization. This edition of the Yearbook will be important reading for anyone involved with teacher education and seeking a contemporary view of what the key issues are in their field and how they might be tackled. The Yearbook includes contributions from authors in 20 countries
Includes reference and index.
Keywords: Teachers -- Training of -- Comparative studies